(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The aim of this paper is to present a new ECG and motion activity monitoring and on-line analysis system for athle- tes. The developed system is intended to facilitate the coach in optimizing and individualizing the training of elite athletes. The hardware system consists of the device for registration of ECG and accelerometer signals and wireless trans- mission to computer. The coach software works in two modes: on-line version is used during training and off-line version is designed for detailed data analysis after training. The new method for respiration frequency evaluation was developed and checked on 28 persons, and in most cases the developed algorithm correctly evaluated the respiration frequency of the investigated persons. The evaluation of athlete’s functional state from calculated and measured pa- rameters and formation of warning signals (green — normal state, yellow — limitary state and red — premonitory state) is based on the analysis applying Moore and Mealy automata algorithms. The software for the evaluation of the patient’s activity was tested on 11 healthy students: the increase in physical activity level during the brisk walk was 1.4 times higher compared to the level during the slow walk, and during the jogging sessions it was 1.89 times higher than during the slow walk. The results obtained during the investigations show that the developed ECG and motion activity monitoring system with two packages of software allows to measure cardio respiratory changes and changes in intensities of physical activity under daily conditions. The comprehensive off-line analysis by monitoring data provides the possibility for coaches to make more detailed analysis of cardio respiratory changes and changes in intensities during training. Keywords: monitoring system for athletes, electrocardiogram, accelerometry, respiration frequency.